2013
DOI: 10.5536/kjps.2013.40.1.041
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Carcass Yield of Heavy Female Broiler at Different Stocking Densities

Abstract: This work was carried out to investigate performance and carcass yield of large-type broiler females at different stocking densities. Chicks (n = 492; 1-day-old; female; Arbor Acre broiler) were reared for six weeks (starter, 0~1 wk; earlier, 1~3 wk; finisher, 3~6 wk) and randomly divided into 3 treatments (4 replications/treatment, 36, 41 or 46 birds/replication). Treatments were T1 (10.9 birds/m 2 ), T2 (12.4 birds/m 2 ) and T3 (13.9 birds/m 2 ) by the stocking densities. Research indexes were livability, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The carcass rate was reported to be 65% of the live weight in 1995, according to National Institute of Animal Science (NIAS) [ 11 ], which was rather different from the results obtained in this study. However, the carcass rates reported in 2010 and 2015 were 71% at 30 days of slaughter age [ 12 , 13 ] and were more consistent with the current results. Additionally, the breeding performance investigated in this study was found to be similar to that of other countries given the same raising period [ 3 , 14 ], which suggested that the Korean broiler productivity indicators improved significantly.…”
Section: Resultssupporting
confidence: 90%
“…The carcass rate was reported to be 65% of the live weight in 1995, according to National Institute of Animal Science (NIAS) [ 11 ], which was rather different from the results obtained in this study. However, the carcass rates reported in 2010 and 2015 were 71% at 30 days of slaughter age [ 12 , 13 ] and were more consistent with the current results. Additionally, the breeding performance investigated in this study was found to be similar to that of other countries given the same raising period [ 3 , 14 ], which suggested that the Korean broiler productivity indicators improved significantly.…”
Section: Resultssupporting
confidence: 90%